Prospecting the briquette as a sustainable technological product (Research, Society and Development, 2025)
Concern about waste disposal from numerous industrial processes is latent, especially given the difficulty of recovering many non-renewable energy sources, including fossil fuels. The disposal of urban waste has challenged public authorities and society to devise new alternatives. The present study aims to investigate the technological product briquette (a subgenre of biomass), which consists of the densification of waste that is useless in industry and in urban areas. The research methodology will be a mixed study that uses part of a literature review and part of a case study. For the review, the focus was on briquettes, with an emphasis on their composition, product cycle, potential customers, material quality and calorific value, sustainable, political and social aspects, using the SCOPUS database and the database provided by CAPES, using the keywords: Briquette; For prospecting, the following databases will be used: Lens and Espacenet, using the keyword: Briquette.